Cardiorespiratory Polygraphy for Detection of Obstructive Sleep Apnea in Patients With Atrial Fibrillation - Delesie, Michiel; Knaepen, Lieselotte; Verbraecken, Johan; Weytjens, Karolien; Dendale, Paul; Heidbuchel, Hein; Desteghe, Lien (Frontiers in Cardiovascular Medicine, 2021)
Background: Obstructive sleep apnea (OSA) is a modifiable risk factor of atrial fibrillation (AF) but is underdiagnosed in these patients due to absence of good OSA screening pathways. Polysomnography (PSG) is the gold standard for diagnosing OSA but too resource-intensive as a screening tool. We explored whether cardiorespiratory polygraphy (PG) devices using an automated algorithm for Apnea-Hypopnea Index (AHI) determination can meet the requirements of a good screening tool in AF patients. Methods: This prospective study validated the performance of three PGs (ApneaLink Air (ALA), SOMNOtouch RESP (STR) and SpiderSAS (SpS)) in consecutive AF patients who were referred for PSG evaluation. Patients wore one of the three PGs simultaneously with PSG, and each PG during three consecutive nights at home. Severity of OSA was classified according to the AHI during PSG (<5= no OSA, 5-14= mild, 15-30= moderate, >30= severe). Results: Of the 100 included AF patients, PSG diagnosed at least moderate in 69% and severe OSA in 33%. Successful PG execution at home was obtained in 79.1%, 80.2% and 86.8% of patients with the ALA, STR and SpS, respectively. For the detection of clinically relevant OSA (AHI ≥15), an area under the curve of 0.802, 0.772 and 0.803 was calculated for the ALA, STR and SpS, respectively. Conclusions: This study indicates that home-worn PGs with an automated AHI algorithm can be used as OSA screening tools in AF patients. Based on an appropriate AHI cut-off value for each PG, the device can guide referral for definite PSG diagnosis.